Sudden stratospheric warmings seen in MINOS deep underground muon data - Osprey, S; Barnett, J; Smith, J; Adamson, P; Andreopoulos, C; Arms, K; Armstrong, R; Auty, D; Ayres, D; Baller, B; Jr, B; Barr, G; et al. (2009)
The rate of high energy cosmic ray muons as measured underground is shown to be strongly correlated with upper-air temperatures during short-term atmospheric (10-day) events. The effects are seen by correlating data from the MINOS underground detector and temperatures from the European Centre for Medium Range Weather Forecasts during the winter periods from 2003-2007. This effect provides an independent technique for the measurement of meteorological conditions and presents a unique opportunity to measure both short and long-term changes in this important part of the atmosphere. Copyright 2009 by the American Geophysical Union.